Hands-On Dashboard Development with QlikView : Practical Guide to Creating Interactive and User-Friendly Business Intelligence Dashboards. - Agarwal, Abhishek (Packt Publishing Ltd, 2019)
The book will help you build effective business intelligence dashboards using the latest features of QlikView. You will create different types of visualizations such as bar charts, interactive plots, and more. With this book, you will learn how to gain actionable insights from your data and communicate them across to relevant stakeholders in ...